Business partnership at the information technology sector in Brazil - Albuquerque, D. C.; Filipe, J. A.; Ferreira, M. A. M. (International Journal of Latest Trends in Finance and Economics Sciences, 2015)
This article is made up of a case of application of Game Theory to business partners. It analyzes the partnership as an element that has consequences on the sustainable growth process of companies in the Information Technology (IT) industry in Brazil and presents the application of a model adopted by business partners on this sector. Research shows that partnership between IT companies with complementary profiles has beneficial effects and contributes to the sustainable growth of the companies in the IT sector, and consequently to this technology sector in Brazil.